Do mothers dream of electric babies? the importance of emotional bonds for growing, nuturing, and educating - Mieli, Giuliana (Routledge, 2019)
We live in a society that ignores and disregards attachment needs and feelings. Starting from this consideration, the author describes the stages of human emotional development in a lucid narrative which is both scientifically rigorous and grounded in clinical examples. Mieli critically investigates the origins of a specific weariness towards feelings which is reflected in the history of Western philosophy and science, resulting in a cultural disregard of emotional needs. The book powerfully suggests that if undeterred, this disregard may lead to severe consequences for the future of our society. Research compellingly shows that responding to fundamental emotional needs is a psycho-biological requirement necessary for human wellbeing and survival itself. Mieli contends that its oversight has a counterpart in the dramatic rise of mental distress in contemporary society, as well as in the difficulties that are increasingly encountered around maternity, fertility, and parenting